Human Resource Management Between Economy and Ethics – Research of Serbia and Bosnia and Hercegovina - Azra Hanić; Dragana Jevtić (Business Ethics and Leadership)
This paper discusses economic and ethical issues that bring about certain limitations in human resource management as one of the basic organizational functions, through which the organization’s relationship with employees is expressed. The aim of this paper is to point out the ethical dimension of human resource management as a key organizational function, which has economic, but at the same time ethical responsibilities. In elaborating this problem, we started from the basic assumption that human resource management as an organizational function and theoretical concept should balance between economic and ethical requirements, which depends on the attitudes of managers as decision makers. In addition to the analysis of the existing literature in this field, an empirical research was conducted to verify the stated assumptions on the basis of a survey questionnaire, which explored the attitudes of managers. The results were processed by statistical methods in the SPSS program. The significance of this paper derives from the importance of employees for the organization and the sensitivity of the human dimension of the organization in relation to the economic one. Bad condition in human resources management in BiH and Serbia, as the countries on which our research is focused, with unfavorable situation on the labor market, low level of perception of needs by managers and knowledge (professionalism) required for experts in this field to achieve necessary influence and affirm an effective concept and practice, opens opportunities for unethical actions of organizations. Unethical practices can be generated by ignorance, employers ’greed for quick profits, and weak institutional influence. High distance of power is an unfavorable cultural factor that encourages the arbitrariness of individuals and prevents social control of the behavior of organizations. In these wanderings and undefined directions of institutional development, in these countries there is room for corruption, poor law enforcement (incomplete reform of the judicial system), insufficiently defined protection of private property, strong influence of political parties in all spheres of life, political and economic connection, significant share of state property, etc. On the ground of egalitarian culture, high social inequality and impoverishment of the majority of the population is created, which negatively affects education, health and distracts attention from the civic control of the government. Therefore, in the research we started from the assumption that the primary evaluation of the human and social function of business and employees as a purpose, not a means, positively affects the ethical practice of human resource management, which we tested over the average response of respondents employed in different positions in the organization. The results obtained are presented in the paper.